Evasão e evadidos nos cursos de graduação da UFMG - Ana Amelia Chaves Teixeira Adachi (2009)
This research intends to analyze the student's dropout in five undergraduate courses of the Federal University of Minas Gerais - UFMG, from 2000 to 2007. The study is characterized by being a case study and the chosen methodology considered the existent information in the Registration and Academic Control Department - DRCA of UFMG, the institutional rules for the students' disconnection and the data collected in interviews with the former-students, avoided and no- avoided. The found results, by a quantitative and qualitative information analysis, show that escape is higher in the courses that demand lower notes for entrance, in graduations whose students socioeconomic and cultural level is predominantly low and the courses present lower social prestige. The students with low socioeconomic classification, the ones which receive support of the student attendance, present high conclusion indexes. Students of five courses were selected to be interviewed. The intension was to identify their reasons to abandon the courses. The main detected aspects were the acting problems, because they are hard-working students and they had high school done out of Belo Horizonte.